Risk Framework for Open Source Applications Using Agent Oriented Modelling - Teh, J.; Bhuiyan, M.; Prasad, P.; Krishna, Aneesh (2016)
This paper aims to propose a novel risk framework utilizing agent oriented modelling in order to provide guidelines for the adoption of Open Source Software (OSS) solutions to an organization. Multiple studies have focused on user requirements and technical aspects when implementing OSS solutions. However, there is a lack of literature focusing on the social aspects of ‘why’ and ’how’ risks of OSS adoption can impact the overall organizational goals and the OSS ecosystem. Therefore, another focus area of this work is to bridge the gap between actors (goals, softgoals, task, and resources) and risk factors when adopting OSS in the organization by proposing new risk measurement and risk prioritization methods. This study is based on literature survey and a case study on OSS adoption in an organization. The research results show that the proposed risk measurement validates the current methods while providing deeper insights into the criticality and strong relationship between actors which in turn assists in proposing appropriate risk response strategies such as delegation of risk among these actors. The result implies that taking ecosystems into consideration is important for risk mitigation.